Rhizospheric actinobacteria of Opuntia sp. “prickly pear” with deaminase activity as growth promoting in Solanum lycopersicum L. under salinity stress - Sánchez-Purihuamán, Marilín (2023)
The growing of Solanum lycopersicum L. "tomato" is affected by salinity, reducing its water consumption, and affecting negatively plant growth and development. Therefore, it is necessary to seek sustainable cultivation and fertilization options, such as the use of plant growth-promoting rhizobacteria. This research aimed to determine the potential of rhizospheric Actinobacteria isolated from Opuntia sp. "prickly pear" as tomato growth promoting under salinity. The genera of isolated Actinobacteria were identified, the synthesis of 1-aminocyclopropane-1-carboxylic acid deaminase (ACC) was characterized and its effect on the germination of tomato cultivar Río Grande seeds was evaluated. Two tests on non-saline and saline soils were carried out to compare the effect of Streptomyces spp. and Nocardia sp. in plant development in the greenhouse. Several Actinobacteria genera were isolated from 87.03% of samples, highlighting Streptomyces (46.67%) and Nocardia (34.0%). 9.33% of the Actinobacteria presented ACC deaminase activity, which increased seed germination, and the growth and yield of seedlings with increases of 88.98% (height); 96.30% (number of sheets); 201.35% (aerial biomass); 173.77% (root length); 100.0% (root weight); 150.0% (number of fruits) and 173.14% (weight of fruits), as well as 1.37 mg/g in the chlorophyll content in the saline soil. Also, Streptomyces sp. strain 21 decreased sodium content and increased potassium and K+/Na+ rate in the leaves and roots of the plants with the highest yield (1.068 kg/plant) in the saline soil. In conclusion, the positive effect of Actinobacteria as promoters of tomato growth and yield, increasing chlorophyll content, and decreasing salinity stress was demonstrated.